Relaxin and Its Role in the Development and Treatment of Fibrosis - Bennett, Robert G. (2009)
Relaxin, a peptide hormone of the insulin superfamily, is involved in the promotion of extracellular matrix remodeling. This property is responsible for many of the well-known reproductive functions of relaxin. Recent important findings, including the identification of the relaxin receptor and the development of the relaxin-null mouse, have identified new targets and mechanisms for relaxin’s actions, resulting in unprecedented advances in the field. Relaxin has emerged as a natural suppressor of age-related fibrosis in a number of tissues, including the skin, lung, kidney, and heart. Furthermore, relaxin has shown efficacy in the prevention and treatment of a variety of models of experimentally induced fibrosis. The intention of this review is to present a summary of recent advances in relaxin research, with a focus on areas of potential translational research on fibrosis in nonreproductive organs.